Exploring the Potential of Oral History Project (OHP) in enhancing Meta-cognitive Abilities in a History Classroom - Mohau Soldaat; Fezeka Gxwayibeni (E-Journal of Humanities, Arts and Social Sciences, 2025)
The Oral History Project (OHP) is prescribed in the South African History curriculum of Grades 10 and 11 for Term two. Understanding the concept of metacognition through the OHP of the Grade 11 class carries the potential of illuminating the nuanced experiences of both History teachers explaining and learners in doing the project. There is a limited understanding of the concept of metacognition within history education. The purpose of this paper was to explore the potential of OHP’s ability to enhance metacognition. This was approached in two phases, viz. (I) understanding how History teachers hand out and guide learners in the process of doing the project, and (ii) understanding how learners grasp the instruction of doing the project. Methodologically, the case study was employed as a research design wherein 29 Grade 11 learners from a rural school were sampled in Mankweng Circuit, Capricorn District, Limpopo Province, South Africa. The participating school was purposefully sampled as it offers History in the Further Education and Training (FET) phase. Jean Piaget’s cognitive development theory was adopted as a lens to guide this paper. Firstly, the paper recommends that the use of codeswitching should be encouraged in order to enhance the learners’ linguistic proficiency when receiving instruction. Secondly, teachers need continuous training to prepare and train learners to perform the OHP. Lastly, there is a need for learners to be in intense moderation or supervision while doing the project. This paper adds value to the advancement or the growing scholarship of metacognition in history education and decolonising knowledge.